2010
DOI: 10.1063/1.3399152
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel resistance switching in Cu/TaOx/Pt structures induced by a coupled mechanism

Abstract: We report on multilevel bipolar resistance switching in Cu/amorphous-TaOx/Pt structures controlled by a coupled mechanism. The devices could be reproducibly programmed into three nonvolatile resistance states, and the on/off ratios between all neighboring states are >20. It is speculated that the switching between the high resistance state and the intermediate resistance state originates from a phase transformation between Ta2O5 and TaO2, while the low resistance state is induced by the formation of Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…The mechanism of the normal unipolar RS in ECM device has been widely studied, which is dominated by formation and rupture of continuous CF based on Joule heating assisted cation redox reaction. [29][30][31][32][33][34] For abnormal unipolar switching, the electroforming process is achieved at low I CC (10 nA) condition. In this case, the device shows threshold switching characteristic during electroforming process (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of the normal unipolar RS in ECM device has been widely studied, which is dominated by formation and rupture of continuous CF based on Joule heating assisted cation redox reaction. [29][30][31][32][33][34] For abnormal unipolar switching, the electroforming process is achieved at low I CC (10 nA) condition. In this case, the device shows threshold switching characteristic during electroforming process (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The complexity of RS mechanism not only comes from its variety but also from the correlation between different mechanisms [61,62]. Zhang et al [63] reported the coexistence of metallic and hopping conduction at the low resistance state (LRS) of Ta 2 O 5-x /TaO y based RRAM, and three types of conduction behaviors were found by temperature-dependent measurements ranging from 5K to 250K.…”
Section: Complex Mechanismmentioning
confidence: 97%
“…A much simpler alternative to increase storage density in RRAM devices is by making use of multilevel cell (MLC) storage technology which enables storing more than one bit per cell without reducing the physical device dimensions. This MLC is one of the most promising properties of RRAM which can significantly increase the memory storage density [83,[118][119][120][121][122][123][124][125]. Thus, instead of a single high and low resistance state (HRS and LRS), we can achieve multiple HRS and LRS, without changing the device dimensions.…”
Section: Multilevel Per Cell (Mlc) Storagementioning
confidence: 99%